Elucidation of single atom catalysts for energy and sustainable chemical production: Synthesis, characterization and frontier science - Adrian Chun Minh, Loy; Teng, Sin Yong; How, Bing Shen; Zhang, Xixia; Cheah, Kin Wai; Valeria, Butera; Leong, Wei Dong; Bridgid Lai Fui, Chin; Yiin, Chung Loong; Martin J., Taylor; Kyriakou, Georgios (Elsevier Ltd., 2023)
The emergence of single atom sites as a frontier research area in catalysis has sparked extensive academic and industrial interest, especially for energy, environmental and chemicals production processes. Single atom catalysts (SACs) have shown remarkable performance in a variety of catalytic reactions, demonstrating high selectivity to the products of interest, long lifespan, high stability and more importantly high atomic metal utilization efficiency. In this review, we unveil in depth insights on development and achievements of SACs, including (a) Chronological progress on SACs development, (b) Recent advances in SACs synthesis, (c) Spatial and temporal SACs characterization techniques, (d) Application of SACs in different energy and chemical production, (e) Environmental and economic aspects of SACs, and (f) Current challenges, promising ideas and future prospects for SACs. On a whole, this review serves to enlighten scientists and engineers in developing fundamental catalytic understanding that can be applied into the future, both for academia or valorizing chemical processes.